A Biophysical Analysis of Mitochondrial Movement: Differences Between Transport in Neuronal Cell Bodies Versus Processes. (30th April 2014) - Narayanareddy, Babu Reddy Janakaloti; Vartiainen, Suvi; Hariri, Neema; O'Dowd, Diane K.; Gross, Steven P.
<x xml:space="preserve">Abstract</x> There is an increasing interest in factors that can impede cargo transport by molecular motors inside the cell. Although potentially relevant (Yi JY, Ori‐McKenney KM, McKenney RJ, Vershinin M, Gross SP, Vallee RB. High‐resolution imaging reveals indirect coordination of opposite motors and a role for LIS1 in high‐load axonal transport. J Cell Biol 2011;195:193–201), the importance of cargo size and subcellular location has received relatively little attention. Here we address these questions taking advantage of the fact that mitochondria – a common cargo – in Drosophila neurons exhibit a wide distribution of sizes. In addition, the mitochondria can be genetically marked with green fluorescent protein (GFP) making it possible to visualize and compare their movement in the cell bodies and in the processes of living cells. Using total internal reflection microscopy coupled with particle tracking and analysis, we quantified the transport properties of GFP‐positive mitochondria as a function of their size and location. In neuronal cell bodies, we find little evidence for significant opposition to motion, consistent with a previous study on lipid droplets (Shubeita GT, Tran SL, Xu J, Vershinin M, Cermelli S, Cotton SL, Welte MA, Gross SP. Consequences of motor copy number on the intracellular transport of kinesin‐1‐driven lipid droplets. Cell 2008;135:1098–1107). However, in the processes, we observe an inverse relationship between the mitochondrial size and velocity and the run distances. This can be ameliorated via hypotonic treatment to increase process size, suggesting that motor‐mediated movement is impeded in this more‐confined environment. Interestingly, we also observe local mitochondrial accumulations in processes but not in cell bodies. Such accumulations do not completely block the transport but do increase the probability of mitochondria–mitochondria interactions. They are thus particularly interesting in relation to mitochondrial exchange of elements. <inline-graphic xlink:href="ark:/27927/pghmhz09kx" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />